A new species of Drosera section Arachnopus (Droseraceae) from the western Kimberley, Australia, and amendments to the range and circumscription of Drosera finlaysoniana - Krueger, Thilo; Fleischmann, Andreas (Phytotaxa, 2021)
A new annual species of Drosera section Arachnopus, Drosera margaritacea, from the western Kimberley region (Western Australia) is described and illustrated, including detailed comparisons with the morphologically most similar species, D. finlaysoniana. The latter name is lectotypified here. The global range of D. finlaysoniana is provided, including a doubtful first record for Thailand, while the species, in contrast with statements made in some published references, does not occur in India, Laos, Cambodia and the Philippines. Additionally, the first record from Indonesia of the frequently misidentified D. aquatica is reported.